2016
DOI: 10.1177/1040638716658928
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes of platelet and plasma coagulation parameters in young pigs

Abstract: Abstract. The literature on hemostatic processes in swine is sparse and often fragmentary; hence, we conducted our study to characterize age-related changes in selected parameters of primary and secondary hemostasis in 50 growing pigs between day 2 and week 24 of age. We measured platelet count (PLT), mean platelet volume, platelet-to-large cell ratio, prothrombin time, activated partial thromboplastin time (aPTT), thrombin time (TT), and fibrinogen concentration. Among primary hemostasis parameters, PLT under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…In addition, the variations in platelet count were similar to the fluctuation in control or pre-study values, and were of a magnitude of change commonly observed in weaned piglets under similar study conditions [21].…”
Section: Resultsmentioning
confidence: 55%
“…In addition, the variations in platelet count were similar to the fluctuation in control or pre-study values, and were of a magnitude of change commonly observed in weaned piglets under similar study conditions [21].…”
Section: Resultsmentioning
confidence: 55%
“…The minipig has been proposed as an alternative large animal model to the canine and NHP for evaluation of medical countermeasures for treatment of acute radiation syndrome. Development of a coagulopathy-related model would have particular utility in characterizing the underlying mechanisms associated with coagulopathy (Olsen et al 1999;Pliszczak-Krol et al 2016) and associated multi-organ dysfunction (Gando 2010) as well as hemorrhage. This study was conducted as part of the overall BARDA consortium approach to evaluate multiple circulating markers associated with coagulopathy following total body irradiation of the Gottingen minipig.…”
Section: Discussionmentioning
confidence: 99%
“…Pliszczak-Król et al [38] described that PLT variability in piglets may be due to the rapid growth of these animals and the maturation of their hematopoietic system. Despite no differences being found in the PLT concentration, signi cantly lower values were found on day 3 in PCT and MPM for males from ET compared to those derived by AI.…”
Section: Discussionmentioning
confidence: 99%